Fire and roller-chopping effects on forage production, plant diversity, and carbon storage in Neltuma woodlands of the Central Monte, Argentina - Meglioli, Pablo A. (2025)
In dry forests, we face the challenge of maintaining forage production while conserving or enhancing ecosystem services and biodiversity. Management practices such as fire and roller-chopping are commonly used to increase grass production and support cattle grazing. However, cattle can alter forest structure and plant diversity. Despite these practices in the native forests of the Monte desert, their effects on ecosystem function, particularly carbon storage, remain poorly understood. Here, we evaluated the effects of fire and roller-chopping on forest structure, plant diversity, and carbon storage in Neltuma woodlands of southern Mendoza, province, Argentina. We hypothesized that fire, by altering forest structure and reducing plant diversity, would lead to a greater reduction in carbon stocks than roller-chopping, which primarily affects the understory. We estimated carbon stocks in various ecosystem compartments under three forest land uses: reference forests, rolled forests, and burned forests. Our findings highlight how forest management practices modified tree density, canopy cover, and species richness, ultimately hampering carbon storage. Reference forests had the highest carbon storage, especially in trees, roots, and shrubs components, while fire-affected forests showed the lowest carbon stocks. Although no significant differences were observed in pools of herbs, litter, woody debris, and dead plants, reference forests consistently stored more carbon than both rolled or fire-affected forests. Roller-chopping forests exhibited intermediate values of carbon storage for most compartments. These results provide valuable insights for designing silvopastoral management strategies that balance livestock production, biodiversity conservation, and carbon storage.